Structural Equation Modeling of the Mediating Role of Resilience in the Relationship between Cognitive Emotion Regulation Strategies and Psychological Well-Being of Patients with Irritable Bowel Syndrome - Mohammad Reza Tamannaeifar; Zahra Shirani (روانشناسی بالینی و شخصیت)
Introduction: Irritable bowel syndrome (IBS) is a chronic and often debilitating functional disorder characterized by disrupted gut-brain interactions. It poses a significant public health challenge, impacting individuals' work, social participation, and psychological well-being. In this context, the objective of the current study was to examine the structural equation modeling of the mediating role of resilience in the relationship between cognitive emotion regulation strategies and the psychological well-being of patients with irritable bowel syndrome.Method: The current study employed a descriptive and correlational methodology. The statistical population consisted of all patients with irritable bowel syndrome who were referred to the Digestive Health Center at Al-Zahra Hospital in Isfahan in 2023. The sample size of 300 individuals was determined using the Klein model (2023) and the convenience sampling method. The research data collection tools included the Compel Seal, the Resilience Scale (CD-RISC) developed by Austin (2007), the Cognitive Emotion Regulation Questionnaire (CERQ) created by Granofsky et al. (2001), and the Psychological Well-Being Scale (PWBS) designed by Reiff (1989). Statistical analysis of the data was conducted using SPSS and AMOS version 28 software.Results: The research findings indicated that maladaptive cognitive emotion regulation (β = -0.68, p = 0.002) and adaptive cognitive emotion regulation (β = 0.73, p = 0.002) had a direct and significant impact on psychological well-being. Finally, resilience (β = 0.71, p < 0.05) had a direct and significant effect and may serve as an important mediator in the relationship between cognitive emotion regulation strategies and psychological well-being. The final model of the study demonstrated a good fit, with an RMSEA of 0.026 and a p-value of less than 0.05.Discussion and Conclusion: In conclusion, given the significant mediating role of resilience, it is possible to enhance the psychological well-being of patients with irritable bowel syndrome through effective interventions, such as emotion regulation training and resilience training.